Neonatal Outcomes in Women with Non-Reactive Cardiotocography: A Cross-Sectional Study - Uzma Asif, Fiza Jamil, Farzana Sarwar, Tanzila Sarfraz, Qamoos Razzaq (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Non-reactive cardiotocography (CTG) is a well-known indicator of potential fetal distress and has been linked to adverse neonatal outcomes. However, the predictive accuracy of non-reactive CTG remains debated in clinical settings. Objective: This study aims to evaluate neonatal outcomes in women with non-reactive CTG during labour and to assess the association between non-reactive CTG and adverse neonatal outcomes, focusing on clinical decision-making and management. Methods: A cross-sectional study was conducted at a Department of Gyne & Obs Mansoora Teaching Hospital, Lahore from Jan 2023 to July 2023 involving 130 pregnant women with non-reactive CTG from January to June 2024. Data on maternal demographics, obstetric history, mode of delivery, and neonatal outcomes (Apgar scores, birth weight, NICU admission, neonatal mortality) were collected and analyzed using SPSS. Results: Significant associations were observed between non-reactive CTG and low Apgar scores, NICU admissions, low birth weight, and neonatal mortality. Regression analysis confirmed that non-reactive CTG independently predicted adverse outcomes, even after adjusting for confounders. Conclusion: Non-reactive CTG is associated with higher rates of neonatal complications. The results emphasize the need for careful monitoring and timely intervention in women with non-reactive CTG patterns. Keywords: Non-reactive cardiotocography, neonatal outcomes, Apgar score, NICU admission, low birth weight, neonatal mortality.